Perancangan User Experience Aplikasi E-Koperasi Sekolah berbasis Android dengan menggunakan Metode Human Centered Design (HCD) - Lasma Divathama Tobing; Herman Tolle (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
School cooperatives have activities in selling and buying goods needed by everyone in the school environment. These activities make school cooperative officers always provide goods to be sold in school cooperatives. Even so, the number of people who buy goods that support school needs in school cooperatives with limited time becomes an obstacle in carrying out activities in school cooperatives. With these problems, a solution was made that aims to make it easier for buyers and cooperative officers to carry out activities related to school cooperatives. User Experience design is carried out in order to develop applications with high User Experience results. This design is made using the Human Centered Design (HCD) approach where the design is centered on human activities. The design begins by identifying the activities that occur in the school cooperative environment. From the identification results, there are two scenarios that are run by four actors, namely buyers, cashiers, suppliers, and cooperative admins. The two scenarios are the process of buying and selling goods and the process of controlling the goods. The results of the design evaluation using the User Experience Questionnaire (UEQ) in this design received positive scores, especially in the level of Attractiveness, Clarity, Efficiency, and Accuracy. The results of the Heuristic Evaluation show that there are problems in the design that can be fixed. Thus, it can be concluded that the solution design can provide a positive perception in terms of User Experience